Review on Phytochemical and phytotherapeutic properties of Inula racemosa - kumar, Ajit (IJRDO-Journal of Applied Science, 2018)
From ancient times various diseases have treated by using medicinal plants and phyogenic products throughout the world. Crude extracts are now considered a valuble source for natural products used in the development of medicines against various diseases for the development of pharmaceutical preparations and for novel biomedical research. Inula racemosa mostly distributed in Asia in hilly areas. These plants are used for traditional medicine for several years for various diseases. These plants have been used in treating different diseases like gastric irritability, febrifuge, nervous depression, anthelmintic, liver complients, jaundice, sores in eyes and fever etc. The present review aims to present a brief overview of the medicinal use as well pharmacological value of the plants focusing for the current research work on Lung cancer.Keywords: Inula racemosa, Taxonomical classification, Phytochemical constituents and Phytotherapeutic effects